INTERANNUALS VARIATIONS IN DIVERSITY OF FOLIAR MYCOENDOPHYTES OF PISTACIA ATLANTICA FROM DAYATE AIAT (LAGHOUAT, ALGERIA) - A., Zareb, Smail-Saadoun N. (university of eloued جامعة الوادي, 2020)
Endophytic fungi live inside plant tissues and increase their resistance to abiotic and biotic factors. Our work is concerned with interannual variations of mycoendophyte diversity of leaves of Pistacia atlantica Desf. of dayate Aiat, in the region of Laghouat (Algeria) and this for the spring of 2013 and 2016. The morphological identification revealed the presence of 26 fungal genera. The difference in diversity is very significant between the two years of sampling, according to calculated Shannon Weaver indices. Based on principal component analysis, the distribution of these leaf microorganisms is influenced by the climatic conditions of the study area. Aspergillus and Epicoccum are dominant for 2013. In 2016, Aspergillus and Cladosporium dominate. The persistence of Aspergillus gives it an important role in the fight against the stress suffered by the leaf of Pistacia atlantica.
artical
Keywords: Pistacia atlantica Desf., Fungus mycoendophytes, diversity, temperature, precipitation, Laghouat (Algeria).